BASIC OF PLS SEM STEP BY STEP USING SMART - PLS SEM - Md. Fauzi Ahmad@Mohamad (Penerbit UTHM, 2023)
Finally, I manage to complete writing this book. Thanks to God for giving me, patience and inspiration. Structural Equation Modeling or SEM is a second-generation statistical analysis technique for analyzing the inter-relationships among multiple variables in a model. SEM is an extension of the general linear model (GLM) that enables a researcher to test a set of regression equations simultaneously, SEM software can examine complex relationships and models, such as confirmatory factor analysis and second-order latent variables which improves the weaknesses of ordinary least square (OLS) method. There are two ways to proceed with the structural equation modelling (SEM technique) Covariance-based SEM and PLS-SEM. The selection of the method is based on the normality of data and the type of research. PLS SEM method is used for non-normal data and exploratory research. This book provides researchers with the application of PLS SEM through empirical data focusing on quality management. Empirical data will provide a better understanding of SEM application. I believe that this book will be able to help who are in the theories of applying this technique in their research. Hopefully. this book will provide a useful reference for a better understanding of SEM which can lead to implementing successful research for students and researchers. My sincere, thanks to UTHM for giving me the opportunity to write this book, particularly to share my experience and knowledge in this small contribution.